Panorama temático e metodológico das monografias do curso de Biblioteconomia da Universidade Federal do Pará apresentados nos anos de 2014 a 2016 - BARROS, Alberiny Carneiro (2018)
Approaches the scientific production on the monographs of the Library Science Course of the Universidade Federal do Pará. The main objective is to identify the topics, the research approaches and the methodological instruments most present in the research made by students in the period of 2014 to 2016. As specific objectives, aims: to discuss the universe of scientific production, to analyze the bibliometric indicators in the monographs of the graduates of the Library Science Course, from 2014 to 2016, and to highlight the topics, the research approaches and the methodological instruments most used in the respective time period. It is presented as a bibliographical research, having as sources of research articles, books and database. For data collection, it uses documentary research, with quantitative character, applying the bibliometric method, which consists of a simple statistic to tabulate and quantify the bibliometric indicators analyzed in the study. As a result, it confirmes that the graduates of the respective time period, besides addressing several research topics related to the Library Science roots, are aware of the course research lines, however, it highlights that there is a deficit regarding students' learning about the instruments of data and information collection. It concludes that scientific productions in the form of monographs need improvement, and that students need more follow-up in teaching-learning on the subject methodology, in order to develop their skills and competencies through the good application of research approaches and methodological tools.